Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Di MA Al-Ishlahiyah Binjai - Amiruddin; Suci Ramadhani; Nadya Putri Matondang; Sandy Franata Tarigan (UIR Press, 2023)
The principal's strategy greatly influences teacher professionalism, which is carried out by guiding, fostering and providing opportunities for a teacher to be able to develop his profession. The purpose of this research is to find out the principal's strategy in improving teacher abilities, to find out the principal's strategy in using teacher teaching methods, management of teaching materials, the principal's strategy in evaluating teacher success and to find out the state of the principal in order to improve the qualifications of the teaching profession at MA Al- Ishlahiyah Binjai. The approach used in this study is a qualitative approach with descriptive methods. Data collection techniques used by interviews, observation and documentation. The subjects in this study were school principals and teachers at MA Al-Ishlahiyah Binjai. The results of this study indicate that the principal's strategy for increasing teacher professionalism is: 1. The use of methods in learning is carried out by involving a teacher with training activities, scientific activities, such as writing scientific papers in the form of class actions, seminars, motivating teachers to continue their education and conducting supervision, 2. The principal's strategy for evaluating with class supervision is sometimes done suddenly. The results of this evaluation are collected into notes by the school principal and will be conveyed at meeting activities and the Subject Teacher Consultation forum as a follow-up to the evaluation that has been carried out. carrying out a main task, as well as the lack of motivation for a teacher to be able to develop his profession as a teacher.